Velocities of P-waves in the Ukrainian subcrustal mantle - Gordienko, V.V.; Gordienko, L.Ja. (Reports of the National Academy of Sciences of Ukraine, 2017)
The propagation of longitudinal seismic waves in the Ukrainian subcrustal mantle is analyzed. It is shown that, to explain the arrival times of seismic waves on the remote seismic stations when a significant portion of their path passes through the upper mantle, it is necessary to take a velocity model with a low velocity zone under the crust of recent activation zones. The anomaly corresponds to the value predicted in accordance with ideas of the advection-polymorphic hypothesis and is caused by rising the temperature of rocks in the upper mantle compared with the temperatures at the Precambrian platform in the same depth interval. A small degree of melting of mantle rocks is possible.